SAT0422 FIRST-LINE CSDMARD MONOTHERAPY RETENTION IN PSORIATIC ARTHRITIS: METHOTREXATE OUTPERFORMS SULFASALAZINE. (2nd June 2020) - Jacobs, M.; Pouw, J.; Welsing, P.; Radstake, T. R.; Leijten, E.
Abstract : Background: Conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) are the first-line treatment for psoriatic arthritis (PsA), but there is conflicting data regarding their efficacy and scarce reports describing the duration of use (drug retention) of csDMARD in this population. Their position in treatment recommendations is a matter of growing debate due the availability of alternative treatment options with higher levels of evidence. Objectives: To study drug retention and predictors for drug retention among PsA patients receiving first-line csDMARD monotherapy. Methods: Retrospective cohort study in DMARD-naïve adult PsA patients in whom a first csDMARD was prescribed as monotherapy primarily to treat PsA-related symptoms. Main outcome was time to failure of the csDMARD (i.e stopping the csDMARD or adding another DMARD). Results: 187 patients were included, who were mainly prescribed methotrexate (MTX) (n=163) or sulfasalazine (SSZ) (n=21) (Table 1 ). The pooled median time to failure was 31.8 months (IQR 9.04-110). Drug retention was significantly higher in MTX (median 34.5 months; IQR 9.60-123) as compared to SSZ treated patients (median 12.0 months; IQR 4.80-55.7)(p=0.016, log-rank test) (Figure 1 ). In multivariable cox-regression the use of MTX and older age were associated with increased retention. The main reasons for treatment failure were inefficacy (52%) and side-effects (28%) (Figure 2 ). Upon failure, MTX treated patients were more commonly, subsequently treated with a biologic DMARD compared to SSZ (p<0.05). Conclusion: MTX outperformed SSZ as first-line csDMARD monotherapy in DMARD-naïve PsA patients with respect to drug retention in daily clinical practice. References: n.a. Disclosure of Interests: Marleen Jacobs: None declared, Juliette Pouw: None declared, Paco Welsing: None declared, Timothy RDJ Radstake Employee of: TR currently is an employee of AbbVie. At the time of the work described he had no COIs., Emmerik Leijten: None declared